Lactic Acid Bacteria Strains Differently Modulate Gut Microbiota and Metabolic and Immunological Parameters in High-Fat Diet-Fed Mice - Fabersani, Emanuel; Marquez, Antonela; Russo, Matías; Ross, Romina; Torres, Sebastián; Fontana, Cecilia; Puglisi, Edoardo; Medina, Roxana; Gauffin-Cano, Paola (Frontiers in Nutrition, 2021)
Background: Dietary strategies, including the use of probiotics as preventive agents that modulate the gut microbiota and regulate the function of adipose tissue, are suitable tools for the prevention or amelioration of obesity and its comorbidities. We aimed to evaluate the effect of lactic acid bacteria (LAB) with different adipo- and immuno-modulatory capacities on metabolic and immunological parameters and intestinal composition microbiota in high-fat-diet-induced in mice fed a high-fat diet Methods: Balb/c weaning male mice were fed a standard (SD) or high-fat diet (HFD) with or without supplementation with Limosilactobacillus fermentum CRL1446 (CRL1446), Lactococcus lactis CRL1434 (CRL1434), or Lacticaseibacillus casei CRL431 (CRL431) for 45 days. Biochemical and immunological parameters, white-adipose tissue histology, gut microbiota composition, and ex vivo cellular functionality (adipocytes and macrophages) were evaluated in SD and HFD mice. Results: CRL1446 and CRL1434 administration, unlike CRL431, induced significant changes in the body and adipose tissue weights and the size of adipocytes. Also, these strains caused a decrease in plasmatic glucose, cholesterol, triglycerides, leptin, TNF-α, IL-6 levels, and an increase of IL-10. The CRL1446 and CRL1434 obese adipocyte in ex vivo functionality assays showed, after LPS stimulus, a reduction in leptin secretion compared to obese control, while with CRL431, no change was observed. In macrophages from obese mice fed with CRL1446 and CRL1434, after LPS stimulus, lower levels of MCP-1, TNF-α, IL-6 compared to obese control were observed. In contrast, CRL431 did not induce modification of cytokine values. Regarding gut microbiota, all strain administration caused a decrease in Firmicutes/Bacteroidetes index and diversity. As well as, related to genus results, all strains increased, mainly the genera Alistipes, Dorea, Barnesiella, and Clostridium XIVa. CRL1446 induced a higher increase in the Lactobacillus genus during the study period. Conclusions: The tested probiotic strains differentially modulated the intestinal microbiota and metabolic/immunological parameters in high-fat-diet-induced obese mice. These results suggest that CRL1446 and CRL1434 strains could be used as adjuvant probiotics strains for nutritional treatment to obesity and overweight. At the same time, the CRL431 strain could be more beneficial in pathologies that require regulation of the immune system.